Integrated transcriptomic and metabolomic analysis of goose epididymis reveals molecular markers associated with sperm mobility - Xiaofang Ren; Ke Jiang; Jiaxin Yin; Zhigang Ma; Zhifeng Chen; Kun Yang; Shengjun Liu (Poultry Science)
The low fertility of geese has long constrained the development of the geese industry. Sperm quality plays a critical role in fertility, and sperm mobility (SM) serves as a key indicator of sperm quality. However, the molecular mechanisms underlying SM remain largely unexplored. The objective of this study was to identify molecular markers associated with SM in the epididymis of Zi geese (Anser cygnoides L.). The SM of 40 one-year-old ganders was assessed. Based on SM values, six ganders were selected: three with the highest SM (H group: n = 3, SM = 0.43 ± 0.02) and three with the lowest SM (L group: n = 3, SM = 0.10 ± 0.01, P < 0.001). Semen quality parameters, fertility, and hormone levels were measured in both groups. Epididymal tissues from the six ganders were subjected to transcriptomic and metabolomic analyses. Results identified 438 differentially expressed genes (DEGs) between the groups, primarily associated with transmembrane transport of proteins and ions. These DEGs were enriched in pathways such as “alanine, aspartate and glutamate metabolism,” “butanoate metabolism,” and the “PPAR signaling pathway.” Among these, ATP12A, ATP1B4, and CNDP1 were identified as key genes regulating SM. Additionally, 486 metabolites showed significant differences between the groups in both positive and negative ion modes. Integration of transcriptomic and metabolomic data revealed critical gene-metabolite pairs, including CNDP1–citric acid, implicated in SM regulation. Notably, the “arginine biosynthesis” pathway was significantly enriched by both DEGs and differential metabolites. In conclusion, this study provides novel insights into the molecular mechanisms regulating SM in the epididymis and lays a theoretical foundation for geese breeding programs.